Outcomes of Patients Transferred to Tertiary Center by Life-Saving System in Saudi Arabia. A Propensity Score Matching Observational Study - Soliman Mohammed; Alenzi Hanan; Alfenaikh Rehab; Aletreby Ahmed; Alenzi Malak; Alenzi Hend; Gano Jennifer; Alrashed Rana; Altaymani Yasmeen; Al-Odat Mohammed; Aletreby Waleed (The Journal of Critical Care Medicine)
Inter-hospital transfer is intended to provide access to centralized special care for critically ill patients, when resources in their hospitals are not available. However, an empirical gap exists in available evidence, as outcomes of transferred patients to higher centers are inconsistent.